1997
DOI: 10.1159/000201453
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative Colitis in Oman

Abstract: Objective: Inflammatory bowel disease has been reported to have varying frequencies in different parts of the world, and there seem to be significant differences in the disease pattern and clinical course in cases of ulcerative colitis (UC). The aim of the present study was to assess the incidence and disease pattern of UC in Oman. Method: A prospective study, over a period of 8 years (1987-1994), was performed to study 108 patients found to have UC. Results: The annual incidence of UC was 1.35/100,000. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Among the included studies, six were from India, 1217 four from Korea, 1821 seven from Japan, 22–28 eight from China, 2936 three each from Taiwan, 3739 Singapore, 4042 Malaysia, 4345 and Israel, 4648 two from Turkey, 49,50 and one each from Kuwait, 51 Sri Lanka, 52 Jordan, 53 Iran, 54 and Oman. 55 Six studies reported colorectal cancer risk in patients undergoing routine surveillance. 13,17,24,27,28,49 The prevalence of colorectal cancer in ulcerative colitis was available from all studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, six were from India, 1217 four from Korea, 1821 seven from Japan, 22–28 eight from China, 2936 three each from Taiwan, 3739 Singapore, 4042 Malaysia, 4345 and Israel, 4648 two from Turkey, 49,50 and one each from Kuwait, 51 Sri Lanka, 52 Jordan, 53 Iran, 54 and Oman. 55 Six studies reported colorectal cancer risk in patients undergoing routine surveillance. 13,17,24,27,28,49 The prevalence of colorectal cancer in ulcerative colitis was available from all studies.…”
Section: Resultsmentioning
confidence: 99%
“…The mean duration of ulcerative colitis was 8·0 years (SD 3·04). Five studies 21,43,44,51,55 reported no colorectal cancer (table). …”
Section: Resultsmentioning
confidence: 99%
“…Asian patients, in general, have milder disease and are more responsive to treatment compared to Western patients [30,31]. Asian patients also tend to have fewer complications and lower rates of relapse, colorectal cancer, and colectomy [32,33]. These findings might be partially related to the lower pANCA-positive rate in Asian patients compared to Western patients.…”
Section: Discussionmentioning
confidence: 98%
“… 13 In addition, a prospective hospital-based study from Saudi Arabia reported an estimated incidence of 0.5/10 5 and prevalence of 5.0/10 5 for IBD in children between 1993 and 2002. 14 In a prospective study from Oman, 108 patients were diagnosed with UC 15 in the period between 1987 and 1994 with annual incidence of 1.35/10 5 . In 2004, King Khalid University Hospital, Riyadh, Saudi Arabia, published a study describing 77 patients with CD in 20 years.…”
mentioning
confidence: 99%